A Comparative Analysis of “Mei Hua” and “Han Yu” Chinese Language Textbooks: 《梅花》与《汉语》汉语教材对比分析 - Sintia, Antonia; Ina; Afrimonika, Yoanna (Mandarinable: Journal of Chinese Studies, 2025)
The research title of this article is “A Comparative Analysis of “MeiHua” and “HanYu” Chinese Language Textbooks”. There are various types of Chinese Language Textbooks used by elementary school in Indonesia, two of which is “MeiHua” and “HanYu”. But not all the textbooks are completely suitable for Indonesian students, especially since Chinese is taught as a foreign language. In Chinese textbooks there are several important components, one of which is topic and vocabulary. Therefore, this study employs the literature review method and comparative analysis to examine and compare the topics and vocabulary found in the 'MeiHua' Volumes 1–6 and 'HanYu' Volumes 1–6 Chinese language textbooks, using the Chinese Proficiency Grading Standards for International Chinese Language Education as a reference. Based on the result of the research, this article found that the similarities between the two textbooks lie in the topics that frequently appear, while the differences are seen in the scope and focus of the topics taught. In terms of vocabulary, although the amount of vocabulary in both textbooks does not meet certain standards, they are still suitable for the developmental process of learning Chinese at the elementary level. In addition, MeiHua has a more balanced vocabulary distribution and is in line with YCT Level 3 objectives, while Hanyu is more in line with the needs of overseas Chinese students and follows the primary school Chinese syllabus.